Consider the Fibonacci sequence ( F n ) = ( 1 , 1 , 2 , 3 , 5 , 8 , 1 3 , … ) defined recursively by F 0 = 0 ; F 1 = F 2 = 1 ; F n = F n − 1 + F n − 2 for n ≥ 3 . Define a new sequence ( G n ) by G n = F n 2 + F n + 1 2 for n ≥ 0 . Remarkably, G 2 0 1 7 is a Fibonacci number. If G 2 0 1 7 = F k , what is k ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The easiest way is probably to prove, by induction, that { F 2 n = F n + 1 2 − F n − 1 2 F 2 n + 1 = F n 2 + F n + 1 2
Log in to reply
Great! These are "well known" identities of the Fibonacci numbers.
I would prefer to standardize the Fibonacci sequence to F 0 = 0 , F 1 = 1 , … , so that the indexing of formulas remains constant.
Defining F 0 = 0 , the matrix representation of Fibonacci numbers F n is as follows:
( F n + 1 F n F n F n − 1 ) = ( 1 1 1 0 ) n ⟹ ( F n + 1 F n F n F n − 1 ) 2 = ( 1 1 1 0 ) 2 n = ( F 2 n + 1 F 2 n F 2 n F 2 n − 1 )
⟹ F n 2 + F n − 1 2 F n + 1 n + F n 2 ⟹ G n = F 2 n − 1 = F 2 n + 1 = F 2 n + 1
Therefore, G 2 0 1 7 = F 4 0 3 5 ⟹ k = 4 0 3 5 .
Problem Loading...
Note Loading...
Set Loading...
If you generate the first few values of G n , you'll quickly recognize that all of them are Fibonacci numbers; in fact, G n = F 2 n + 1 . Thus, with n = 2 0 1 7 , we get k = 2 ⋅ 2 0 1 7 + 1 = 4 0 3 5 as the answer.
For a more rigorous answer, one must prove the equation G n = F 2 n + 1 . Anyone?